Paddle mechanics differ between on-water and ergometer sprint kayaking - Harbour, E.; McAlpine, P.; Neville, J. (ISBS Proceedings Archive (Michigan), 2021)
This study investigated biomechanical differences between on-water and ergometer kayaking using a custom sensor-equipped paddle. Five elite male kayak sprint athletes performed identical kayak-specific incremental paddle protocols ranging from stroke rate (SR) 30-90 strokes/min on a kayak ergometer and their typical training venue. Sensor paddles and GPS units were used to collect paddle kinetics and boat motion, respectively. Large to very large differences were observed for pull time (Tpull) (d = 5.9 ± 0.39), air time (Tair) (d = 3.7 ± 0.27), mean force (Fmean) (d = 1.06 ± 0.19), peak force (Fpeak) (d = 1.92 ± 0.22), impulse (d = 2.62 ± 0.23), and impulse rate (IR) (d = 2.10 ± 0.21) between environments. Mixed-effects models and Statistical parametric mapping (SPM) analysis revealed variable differences across intensity levels. These results reveal substantial dissimilarities of paddle kinematics and kinetics between ergometer and on-water kayaking.